“Ready for Change”: Pre-service Teacher Perspectives on Diversity Preparation in Rural Appalachia - McCardle, Todd; Milford, Zachary (International Journal of Multicultural Education, 2024)
Through the lens of transformative learning theory, this qualitative study examines how pre-service teachers (PSTs) in a teacher education program in rural Appalachia shared their perspectives on their preparation to work with diverse students. It examines how their lived experiences and their teacher education program impacted their approach to understanding and addressing diverse needs of their students. Results illustrate the unique way the pre-service teachers [re]imagined their program to better equip future PSTs for diverse classrooms. We argue for programmatic approaches to developing a teaching corps prepared for diversity in the classroom and challenging the shortsighted notion that students in rural Appalachia are unwilling to face the realities of diverse classrooms.